Web-Based Learning Media Using Hypertext Markup Language as Course Materials - Hiskia Kamang Manggopa; Christine Takarina Meitty Manoppo; Peggy Veronica Togas; Alfrina Mewengkang; Johan Reimon Batmetan (Faculty of Engineering, Universitas Negeri Yogyakarta, 2019)
Recently, numerous web-based applications with attractive user interface, brand-new and advanced features, and friendly operation are rapidly developed and widely used, particularly in education context. This study aims to produce web-based learning media that are feasible for delivering materials of web programming subject. The course material of this subject is Hypertext Markup Language (HTML).This study is located at Manado State University, at the study program of information and communication technology. The method of this study employs the research and development model. The data were obtained by four questionnaires, including (1) the feasibility testing by the lecturer, (2) the media expert feasibility testing, (3) the materials expert feasibility testing, and (4) the students’ feasibility testing. Based on the experimental results, it can be stated that the developed web learning is considered useful. It can be concluded that the web-based learning media is feasible to be used and effectively improve the quality of learning.